O HABEAS CORPUS COMO INSTRUMENTO DE TUTELA DOS DIREITOS DA PERSONALIDADE - Garcia, Gabriel Pereira (2020)
This research analyzes the legal institute of habeas corpus in the Brazilian civil process, in particular, to survey and validate the hypotheses in which the aforementioned writ procedure can be used in the protection of the protection of personality righ